Innovative Strategies for Nurse Manager Performance Assessment: A Literature Review - Yunita, Sukma; Pasaribu, Masdalifa; Sharfina, Dirayati; Fauziah Silalahi, Yetti; Leini Saragih, Srimis (JINTAN: Jurnal Ilmu Keperawatan, 2025)
The nursing management field encompasses a range of responsibilities and roles, including overseeing staff, coordinating patient care, managing budgets, and ensuring quality and safety standards are met (Mitchell et al., 2022). The nursing management field involves overseeing staff, coordinating patient care, managing budgets, and ensuring quality and safety standards (Kinshella et al., 2020). Factors such as understaffed units and high turnover rates can hinder effective training (Kinshella et al., 2020). Improving service quality, working conditions, and management of the nursing workforce are crucial for fostering good nurse-client relationships (Isangula et al., 2022). Enhancing nursing students' presentation competencies can prepare them to address complex health challenges through critical thinking and effective communication (Haramba, 2023). Implementing programs like the "DelpHi-Standard" can enhance dementia care management by focusing on treatment, medication, and caregiver support (Eichler et al., 2013). Nurse practitioners play a vital role in providing specialized care and making informed decisions in primary healthcare settings (Sivertsen et al., 2022). The importance of nurse manager performance assessment cannot be understated.